Current sedation practice among general dental practitioners and dental specialists in Jordan: an example of a developing country - Alsoleihat, Firas; Al-Shayyab, Mohammad; Ryalat, Soukaina; Dar-odeh, Najla (Therapeutics and clinical risk management, 2013)
The study reported here aimed to identify current sedation practice among general dental practitioners (GDPs) and specialist dental practitioners (SDPs) in Jordan in 2010. Questionnaires were sent by email to 1683 GDPs and SDPs who were working in Jordan at the time of the study. The contact details of these dental practitioners were obtained from a Jordan Dental Association list. Details on personal status, use of, and training in, conscious sedation techniques were sought by the questionnaires. A total of 1003 (60%) questionnaires were returned, with 748 (86.9%) GDPs and 113 (13.1%) SDPs responding. Only ten (1.3%) GDPs and 63 (55.8%) SDPs provided information on the different types of treatments related to their specialties undertaken under some form of sedation performed by specialist and/or assistant anesthetists. Approximately 0.075% of the Jordanian population received some form of sedation during the year 2010, with approximately 0.054% having been treated by oral and maxillofacial surgeons. The main reason for the majority of GDPs (55.0%) and many SDPs (40%) not to perform sedation was lack of training in this field. While some SDPs (26.0%) indicated they did not use sedation because of the inadequacy of sedative facilities. Within the limitations of the present study, it can be concluded that the provision of conscious sedation services in general and specialist dental practices in Jordan is inconsistent and inadequate. This stresses the great need to train practitioners and dental assistants in Jordan to enable them to safely and effectively perform all forms of sedation.